Gastrointestinal Motility and Functional Gastrointestinal Diseases - Kusano, Motoyasu; Hosaka, Hiroko; Kawada, Akiyo; Kuribayashi, Shiko; Shimoyama, Yasuyuki; Zai, Hiroaki; Kawamura, Osamu; Yamada, Masanobu (Current Pharmaceutical Design, 2014)
Digestive tract motility patterns are closely related to the pathophysiology of functional gastrointestinal diseases (FGID), and these patterns differ markedly between the interdigestive period and the postprandial period. The characteristic motility pattern in the interdigestive period is so-called interdigestive migrating contraction (IMC). IMCs have a housekeeping role in the intestinal tract, and could also be related to FGID. IMCs arising from the stomach are called gastrointestinal IMCs (GI-IMC), while IMCs arising from the duodenum without associated gastric contractions are called intestinal IMCs (I-IMC). It is thought that I-IMCs are abnormal in FGID. Transport of food residue to the duodenum via gastric emptying is one of the most important postprandial functions of the stomach. In patients with functional dyspepsia (FD), abnormal gastric emptying is a possible mechanism of gastric dysfunction. Accordingly, delayed gastric emptying has attracted attention, with prokinetic agents and herbal medicines often being administered in Japan to accelerate gastric emptying in patients who have anorexia associated with dyspepsia. Recently, we found that addition of monosodium L-glutamate (MSG) to a high-calorie liquid diet rich in casein promoted gastric emptying in healthy men. Therefore, another potential method of improving delayed gastric emptying could be activation of chemosensors that stimulate the autonomic nervous system of the gastrointestinal tract, suggesting a role for MSG in the management of delayed gastric emptying in patients with FD.
Keywords: Rome III